2020
DOI: 10.1101/2020.03.05.978965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Evolution of Human Cancer Gene Duplications across Mammals

Abstract: Cancer is caused by genetic alterations that affect cellular fitness, and multicellular organisms have evolved mechanisms to suppress cancer such as cell cycle checkpoints and apoptosis.These pathways may be enhanced by the addition of tumor suppressor gene paralogs or deletion of oncogenes. To provide insights to the evolution of cancer suppression across the mammalian radiation, we estimated copy numbers for 548 human tumor suppressor gene and oncogene homologs in 63 mammalian genome assemblies. The naked mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 78 publications
1
24
1
Order By: Relevance
“…Cows, giraffes and tigers weigh much more than an average human, and yet have somatic mutation rates several fold higher, in line with expectation from their lifespans but not their body mass. Altogether, the weak correlation between body mass and somatic mutation rates after correction for lifespan suggests that the evolution of larger body sizes may have relied on alternative or additional strategies to limit cancer risk, as has been speculated (Supplementary Note 2) 23,[49][50][51] . Of note, the low somatic mutation rate of naked mole-rats, unusual for their body mass but in line with their long lifespan (Fig.…”
Section: Methods)mentioning
confidence: 93%
“…Cows, giraffes and tigers weigh much more than an average human, and yet have somatic mutation rates several fold higher, in line with expectation from their lifespans but not their body mass. Altogether, the weak correlation between body mass and somatic mutation rates after correction for lifespan suggests that the evolution of larger body sizes may have relied on alternative or additional strategies to limit cancer risk, as has been speculated (Supplementary Note 2) 23,[49][50][51] . Of note, the low somatic mutation rate of naked mole-rats, unusual for their body mass but in line with their long lifespan (Fig.…”
Section: Methods)mentioning
confidence: 93%
“…Indeed, despite the remarkably high incidence of cervical ribs in lorisids, among 233 neonatal and juvenile deaths of lorisids in zoos, none was found to have a tumor (Simpson et al, 2018). Similarly, in manatees and sloths, cancer rates appeared to be exceptionally low (Galis & Metz, 2003;Tollis et al, 2020). The moderate use of the forelimbs of lorisids makes it unlikely that they will have TOS problems caused by pressure on the nerves and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vicens and Posada ( 15 ) found that genes related to DNA repair and T cell proliferation have evolved under positive selection in mammals. Tollis et al ( 16 ) found that the number of paralogs of human cancer genes across mammals is positively correlated with the species’ life span but not body size. Vazquez and Lynch ( 17 ) reported widespread tumor suppressor gene (TSG) duplications across both large and small Afrotherian species.…”
Section: Introductionmentioning
confidence: 99%